20世纪中国气候变化研究 - 翟盘茂 巢清尘 邹旭恺 (Journal of geographical sciences, 2004)
［1］Chen L X et al.,1991.Preliminary analysis of climatic change during the last 39 years in China.Quarterly Journal of Applied Meteorology,2(2): 164-174.(in Chinese) ［2］Fu C,2003.Potential impacts of human-induced land cover change on East Asia monsoon.Global and Planetary Change,37: 219-229. ［3］Fu C B,Wen G,1999.Variation of ecosystems in East Asia in association with the seasonal,interannual and decadal monsoon climate variability.Climatic Change,43: 477-494. ［4］Gong D Y,Shi P J,He X Z,2002.Spatial features of the coupling between spring NDVI and temperature over Northern Hemisphere.Acta Geographica Sinica,57(5): 505-514.(in Chinese) ［5］Gong D Y,Wang S W,1999.Impact on global and China′s surface precipitation of ENSO during recent 100years.Chinese Science Bulletin,44(3): 315-320.(in Chinese) ［6］Gong D Y,Wang S W,1999.Influence of atmospheric oscillations on Northern Hemispheric temperature.Geographical Research,18(1): 31-38.(in Chinese) ［7］Gong D Y,Wang S W,1999.Long-term variability of the Siberian High and the possible connection to global warming.Acta Geographica Sinica,54(2): 125-133.(in Chinese) ［8］Gong D Y,Wang S W,2003.Influence of Arctic Oscillation on winter climate over China.Acta Geographica Sinica,58(4): 559-568.(in Chinese) ［9］Gong D Y,Zhu J H,Wang S W,2002.Significant relationship between spring AO and the summer rainfall along the Yangtze River.Chinese Science Bulletin,47(11): 948-951.(in Chinese) ［10］Groisman PYa,Easterling D,1994.Variability and trends of total precipitation and snowfall over the United States and Canada.J.Climate,7: 184-205. ［11］Guo Q Y,1983.The summer monsoon intensity index in East Asia and its variation.Acta Geographica Sinica,38(3): 207-217.(in Chinese) ［12］Guo Q Y,Cai J N,Shao X M et al.,2003.Interdecadal variability of East-Asian summer monsoon and its impact on the climate of China.Acta Geographica Sinica,58(4): 569-576.(in Chinese) ［13］Ho C-H,Lee J-Y,Ahn M-H et al.,2003.A sudden change in summer rainfall characteristics in Korea during the late 1970s.Int.J.Climatol.,23: 117-128. ［14］Huang R H,Xu Y H,Zhou L T,1999.The interdecadal variation of summer precipitations in China and the drought trend in North China.Plateau Meteorology,18(4): 465-476.(in Chinese) ［15］IPCC,2001.Climate Change 2001: The Science of Climate Change.In: Houghton J T,Ding Y,Griggs D J et al.(eds.),Contribution of Working Group I to the Third Assessment Report of the Intergovernmental Panel on Climate Change.Cambridge,United Kingdom & New York,NY,USA: Cambridge University Press,156-159. ［16］Jiang Z H,Ding Y G,1994.Regional features of interannual variation of rainfall over China in the past 4 decades.Journal of Nanjing Institute of Meteorology,17(1): 75-79.(in Chinese) ［17］Kerr R A,1999.A new force in high-latitude climate.Science,284: 241-242.Li Q X,Liu X N,Li X Q,2002.Drought trend in North China in recent half century.Journal of Natural Disasters,11(3): 50-56.(in Chinese) ［18］Li X W,Zhou X J,Li W L,1995.The cooling of Sichuan Province in recent 40 years and its probable mechanisms.Acta Meteorologica Sinica,9(1): 57-68. ［19］Lin X C,Yu S Q,Tang G L,1995.Series of average air temperature over China for the last 100-year period.Scientia Atmospherica Sinica,19(5): 525-534.(in Chinese) ［20］Lu R Y,2003.Liner relationship between inter-annual and inter-decadal variation in flood season precipitation in North China.Chinese Science Bulletin,48(7): 718-722.(in Chinese) ［21］Ma Z G,Fu C B,2001.Trend of surface humid index in the arid area of Northern China.Acta Meteorologica Sinica,59(6): 737-746.(in Chinese) ［22］Ma Z G,Fu C B,2003.Interannual characteristics of the surface hydrological variables over the arid and semi-arid areas of northern China under global warming.Global and Planetary Change,37: 189-200. ［23］Menon S,Hansen J,Nazarenko L et al.,2002.Climate effects of black carbon aerosols in China and India.Science,297: 2250-2253. ［24］National Climate Center,1998.Severe Flood in China.Beijing: Meteorological Press,78pp.(in Chinese) ［25］Qian W H,Hu Q,Zhu Y F et al.,2003.Centennial-scale dry-wet variations in East Asia.Climate Dynamics,21:77-89. ［26］Ren F M,Zhai P M,1998.Study on changes of China′s extreme temperatures during 1951-1990.Scientia A tmospherica Sinica,22(2): 217-227.(in Chinese) ［27］Ren G Y,Wu H,Chen Z H,2000.Spatial patterns of change trend in rainfall of China.Quarterly Journal of Applied Meteorology,11(3): 322-330.(in Chinese) ［28］Sha W Y,Shao X M,Huang M,2002.Climate warming and its impact on natural regional boundaries in China in the 1980s.Science in China (Series D),45(12): 1099-1113.(in Chinese) ［29］Shi N,Zhu Q G,Wu B G,1996.The East Asian summer monsoon in relation to summer large scale weather-climate anomaly in China for last 40 years.Scientia Atmospherica Sinica,20(5): 575-583.(in Chinese) ［30］Shi N et al.,2000.A preliminary study of the northern winter SLP climate base state and its climate variability and effects.Chinese Journal of Atmospheric Sciences,20(5): 575-583.(in Chinese) ［31］Shi Y F,Shen Y P,Hu R J,2002.Preliminary study on signal,impact and foreground of climatic shift from warm-dry to warm-humid in Northwest China.Journal of Glaciology and Geocryology,24(3): 219-226. ［32］Thompson,D W J,Wallace J M,1998.The Arctic Oscillation signature in the wintertime geopotential height and temperature fields.Geophys.Res.Lett.,25: 1297-1300. ［33］Tu Q P,1984.Trend and periodicity of temperature change in China during the last hundred years.Journal of Nanjing Institute of Meteorology,7(2): 151-161.(in Chinese) ［34］Tu Q P,1987.Variation of precipitation over China in the past 100 years.Journal of Nanjing Institute of Meterology,10(2): 177-187.(in Chinese) ［35］Wallace J M,2000.North Atlantic Oscillation/Annular Mode: two paradigms-one phenomenon.Quart.J Royal Met.Soc.,126(564): 791-805. ［36］Wang S W,1990.Variation of temperature in China for the 100 year period in comparison with global temperatures.Meteorological Monthly,16(2): 11-15.(in Chinese) ［37］Wang S W,2001.Progress on Modern Climatology.Beijing: Meteorological Press,472pp.(in Chinese) ［38］Wang S W,Gong D Y,1999. ENSO events and intensity in the recent 100 years. Meteorological Monthly,25(1):9-13. (in Chinese) ［39］Wang S W,Gong D Y,2000. Enhancement of the warming trend in China. Geophys. Res. Lett.,27 (16):2581-2584. ［40］Wang S W et al.,2003. 2002 is the second warmest year in the recent 100 years. Climate Change Newsletter,3:11-12. (in Chinese) ［41］Wang S W,Gong D Y,Ye J L et al.,2000. Seasonal precipitation series of eastern China since 1880 and the variability. Acta Geographica Sinica,55(3): 281-293. (in Chinese) ［42］Wang Z W, Zhai P M, 2003. Variation of drought over northern China during 1950-2000. Journal of Geographical Sciences, 13(4): 480-487. ［43］Xu Q, 2001. Abrupt change of the mid-summer climate in central east China by the influence of atmospheric pollution. A tmospheric Environment, 35(20): 5029-5040. ［44］Yan Z W, Zhang M L, 1992. On change of China′s temperature and its daily range in the recent years. Chinese Science Bulletin, 38(14): 1295-1298. (in Chinese) ［45］Yang H J, Zhang Q, 2003. On the decadal and interdecadal variability in the Pacific Ocean. Advances in Atmospheric Sciences, 20(2): 173-184. ［46］Yao T D et al., 2000. Amplitude of climatic change in Qinghai-Tibetan Plateau. Chinese Science Bulletin, 45(13). ［47］Ye D Z, R Huang H, 1996. Investigation on laws and causes of droughts and floods in the Yellow and Yangtze river valleys of China. Jinan: Shandong Science and Technology Press, 387pp. (in Chinese) ［48］Zhang X, Vincent L A, Hogg W D et al., 2000. Temperature and precipitation trends in Canada during the 20th Century. A tmosphere-Ocean, 38: 395-429. ［49］Zhang X G, Li X Q, 1982. Some characteristics of temperature variation in China in the present century. Acta Meteorologica Sinica, 40(2): 198-208. (in Chinese) ［50］Zhai P M, Ren F M, 1999. On change of China′s maximum and minimum temperatures in 1951-1990. Acta Meteorologica Sinica, 13(2): 278-290. ［51］Zhai P M, Sun A, Ren F et al., 1999. Changes of climate extremes in China. Climatic Change, 42: 203-218. ［52］Zhai P M, Pan X H, 2003. Trends in temperature extremes during 1951-1999 in China. Geophys. Res. Lett., 30(17): 1913. ［53］Zhao Z G, 1996. Influence of El Nino phenomenon on general circulation and China′s precipitation. Atmospheric Science, (4): 422-428. (in Chinese) ［54］Zhao Z C, 2003. The recent hot study on climate change: introduction of IUGG 2003. Climate Change Newsletter,2(4): 14-15. (in Chinese) ［55］Zheng Y Q, Qian Y F, Miao M Q, 2002. The effects of vegetation change on regional climate Ⅰ: simulation results. Acta Meteorologica Sinica, 60(1): 1-16. (in Chinese) ［56］Zhu Q G et al., 1997. The long-term change of atmospheric active centers in northern winter and its correlation with China climate in recent 100 year. Acta Meteorologica Sinica, 55(6): 750-758. (in Chinese)